Investigating the preparation of oxime derivatives of azacrown ethers containing piperidine-4-one heterocycles under microwave irradiation - Tung H. To; Hieu D. Nguyen (Vietnam Journal of Science, Technology and Engineering, 2026)
The use of multi-component reactions to simultaneously synthesise crown ethers and nitrogen-containing heterocycles is a synthetic approach that has attracted significant interest. With nitrogen heterocycles embedded in their structures, azacrown ethers can participate in various reactions to modify their structures for diverse applications. Herein, the preparation of azacrown ethers containing the piperidine heterocycle, based on a modified Petrenko-Kritschenko condition, is reported. The oximation of azacrown compounds was investigated under conventional reflux conditions and microwave irradiation at different temperatures. Physicochemical analyses, including 1 HNMR, 13CNMR, and HRMS, were employed to elucidate the structures of the synthesised compounds. The experimental data demonstrated that microwave irradiation is an effective approach for oximation, reducing the reaction time to 20 minutes at 80°C and affording high yields (89-92%).